L'inconstitutionnalité des pouvoirs du protonotaire spécial - Bouchard, Serge; Lavigne, Marie-Michèle; Renauld, Pascal (Les Cahiers de droit, 1981)
The office of special prothonotary was created in 1975 by an amendment to the Code of Civil Procedure. The main purpose of the change was to ease the administration of justice before the courts. For this reason, the special prothonotary received many assignments which were reserved until then to a judge sitting in chambers and even to the court itself. Such transfer of duties and powers may conflict with section 96 of the BNA Act, which acts as a bar to prevent the withdrawal of judicial functions from a superior, county or district court. This paper deals with the interferences between various sections of the Code of Civil Procedure and section 96 of the BNA Act. The first part of the paper deals with the approach adopted by the courts. The true test, according to the case-law, is to determine the nature of the function involved. Since only judicial functions are protected by section 96, it is intravires the Legislature of Quebec to confer on a board or tribunal administrative or ministerial powers. If the transfer involves judicial functions, the courts will use the test adopted by the Privy Council in Labour Relations Board of Saskatchewan v. John East Iron Works and by Sir Lyman Duff in In re Adoption Act, and examine whether the transferee is analogous to a superior, district or county court. The courts will also have to apply the « 1867 statute books test » : was the particular function conferred to the prothonotary before 1867 ? If the results of each of the two tests are affirmative, then the function is one protected by section 96 of the BNA Act and its transfer is ultra vires the provincial Legislature. If the results are negative, the courts will examine if the provisions involved have the effect of vesting in the special prothonotary the powers of a superior court judge. If the courts conclude that it is so, then, the assignment is ultra vires the powers of the provincial Legislature. The second part deals with each of the assignments transferred to the special prothonotary. These are threefold in nature: 1. Actions by default to appear or by default to plead under article 195 C.C.P. ; 2. Jurisdiction under article 44.1(1) C.C.P. ; 3. Interlocutory or incidental proceedings, contested or not, but, if so, with the consent of the parties. The paper concludes that most of the provisions dealing with the duties and powers of the special prothonotary are unconstitutional